THE EFFECT OF GREEN ACCOUNTING, CASH HOLDING, AND SALES GROWTH ON THE FINANCIAL PERFORMANCE OF CONSUMER NON-CYCLICALS COMPANIES IN INDONESIA: PENGARUH GREEN ACCOUNTING, CASH HOLDING, DAN SALES GROWTH TERHADAP KINERJA KEUANGAN PERUSAHAAN CONSUMER NON-CYCLICALS DI INDONESIA - Michel; Putri Wahyuni (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2025)
This study aims to determine the effect of Green Accounting, Cash Holding, and Sales Growth on the Financial Performance of Consumer Non-Cyclical companies listed on the Indonesia Stock Exchange. This study uses a quantitative method with secondary data sources. The population in this study is 30 companies in the Consumer Non-Cyclical sector listed on the Indonesia Stock Exchange. The sample of this study consists of 14 companies from the 2020-2024 period, totaling 70 samples, using a purposive sampling technique. Data analysis used includes descriptive statistics, classical assumption tests, multiple regression analysis, partial (t-test) and simultaneous (F-test) hypothesis testing, and determination coefficient tests. The results show that Green Accounting has a significant effect on Financial Performance with a calculated t-value of -2.843 < t-table -2.00856 and a significant value of 0.001 < 0.05. Cash Holding has a significant effect on Financial Performance with a calculated t-value of -3.217 < t-table -2.00856 and a significant value of 0.007 < 0.05. Sales Growth has no effect and is not significant on Financial Performance with a calculated t-value of 0.553 < t-table 2.00856 and a significant value of 0.583 > 0.05. Simultaneously, Green Accounting, Cash Holding, and Sales Growth have a significant effect on the Financial Performance of Consumer Non-Cyclicals companies with a calculated F-value of 4.437 > F-table 2.79 with a regression coefficient value of 16.5%.